Catalytic degradation of Acid Orange 7 in water by persulfate activated with CuFe2O4@RSDBC - Kun Guan; Peijiang Zhou; Junye Zhang; Longlong Zhu (Materials Research Express, 2020)
In this study, a novel series of rectorite/sludge derived biochar (RSDBC) supporting CuFe _2 O _4 (CuFe _2 O _4 @RSDBC) composites were prepared as an effective catalyst to active persulfate (PS) for the removal of Acid Orange 7 (AO7) in water. The character of catalyst was analyzed by scanning electron microscope (SEM), transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR) and x-ray diffraction (XRD). Various influencing factors including initial pH, PS concentration, catalyst dosage, initial dye concentration and reaction temperature were investigated. The optimal reaction conditions were found to be: PS concentration 2 mM; catalyst dosage 0.6 g l ^−1 ; initial pH value 7.0 and 25 °C of reaction temperature. Further radical quenching tests were performed by using ethanol, tert-butanol (TBA) and benzoquinone (BQ), which confirmed that sulfate radicals ( ${{{\rm{SO}}}_{4}}^{· -}$ ) and hydroxyl radicals (HO•−) were the reactive species in the degradation process. The Gas chromatography-mass spectrometry (GC-MS) analysis was employed to determine the intermediate products and a plausible degradation pathway is proposed. In addition, the CuFe _2 O _4 @RSDBC sample exhibited high color removal ability (95%) and stable performance after three successive runs. At last, the catalyst proved a good removal effect for actual dye wastewater. These results indicate that CuFe _2 O _4 @RSDBC hybrids could be as effective catalysts for PS activation on dye pollutants elimination.